The Influence of Foreign Language Proficiency on the Uptake of Written Corrective Feedback - Britney M. Paris (Canadian Society for Studies in Education, 2020)
Written Corrective Feedback (WCF) is commonly used in second and foreign language classroom contexts to provide students with feedback on the accuracy of their writing. However, it is unclear whether the proficiency level of the student influences the effectiveness of this feedback. This study investigates the influence of learner proficiency on the effectiveness of two different types of WCF: direct feedback and indirect feedback. This study employs an embedded, mixed methods design in which seven participants provided three writing samples and received two different types of feedback. After each writing sample, the participants participated in think aloud interviews, followed by a retrospective, semi-structured interview. The findings suggest that learner proficiency does not influence the effectiveness of the different feedback types, but that learner proficiency level can influence the students' affective responses to feedback. The study also revealed that beginner and advanced students lack effective strategies for taking up feedback.